Social inequalities in the distribution of social capital indicators among internet users and non-users - Linardis, Apostolos; Fragoulis, George (The Greek Review of Social Research, 2022)
In this article we explore two dimensions of social capital, in particular social trust and the informal networks of internet users and non-users. For this purpose, we use empirical data from the 3rd wave of the World Internet Project (WIP) which took place in 2019. Data analysis shows that internet users have greater stock of social capital compared to the non-users, with regards to both dimensions of social capital, i.e. social trust and informal networks. However, data analysis also shows that the use of internet is not directly connected to most indicators of social capital. Instead, the use of internet is connected to users’ socio-economic and demographic characteristics, which eventually differentiate the distribution of social capital.